LEGAL STATUS OF SPORTS FEDERATIONS - Aliqulov Akmal Akramovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In our country, civil society institutions, non-profit organizations have an important place in the protection of human rights and interests, serving to ensure the balance of interests in society by creating conditions for citizens to realize their potential, increase their social, economic activity and legal culture. At present, today’s tense times , life itself, are setting new, very important and urgent tasks for the upbringing of our youth. Undoubtedly, the role of sports organizations in the implementation of these urgent tasks is incomparable. Therefore, the study of the concept, theoretical foundations, history and types of sports organizations as a subject of international law serves to research in the right direction. It divides sports organizations into international and national organizations. This is due to the fact that the international sports movement aimed at developing sports and strengthening international cooperation in the field of sports, which is considered one of the most important means of the physical and spiritual development of the individual, was also organized with the advent of international sports organizations. While sports organizations are registered in a particular state, international sports is a member of the organization and follows its legal acts.